Household Recordkeeping as Family Records Continuity and Resilience Infrastructure - Okeu Yulianasari; Yanti Shantini; Asep Saepudin; Raistiwar Pratama (Record and Library Journal, 2026)
Background of the study: Household recordkeeping supports access to civil rights, public services, and recovery after disruption, yet family records management remains marginal in records and information scholarship. Purpose: This study synthesizes how household recordkeeping practices are described, what factors shape family records continuity, and what interventions are proposed to support households as recordkeeping units. Method: Following PRISMA 2020, this systematic literature review searched Scopus and SpringerLink for open access English-language journal articles published between 2015 and 2025. Inclusion criteria were open access English-language journal articles published in 2015–2025 that addressed household or family-level records, document management, disruption, disaster, service access, or records continuity. After deduplication, 19 studies were included and analyzed using thematic synthesis. Findings: The findings show that family records function as administrative, legal, social, and symbolic resources managed through creation, organization, storage, access, and reuse. Continuity is shaped by information and digital literacy, socioeconomic resources, infrastructure, institutional accessibility, policy arrangements, and social support. Existing interventions remain limited and focus mainly on guidance, training, and service redesign. Conclusion: This review positions household recordkeeping as resilience infrastructure for sustaining family records continuity.